2012
DOI: 10.1073/pnas.1211946109
|View full text |Cite
|
Sign up to set email alerts
|

Low intravascular pressure activates endothelial cell TRPV4 channels, local Ca 2+ events, and IK Ca channels, reducing arteriolar tone

Abstract: Endothelial cell (EC) Ca 2+ -activated K channels (SK Ca and IK Ca channels) generate hyperpolarization that passes to the adjacent smooth muscle cells causing vasodilation. IK Ca channels focused within EC projections toward the smooth muscle cells are activated by spontaneous Ca 2+ events (Ca 2+ puffs/pulsars). We now show that transient receptor potential, vanilloid 4 channels (TRPV4 channels) also cluster within this microdomain and are selectively activated at low intravascular pressure. In arterioles pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
282
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(299 citation statements)
references
References 29 publications
12
282
0
Order By: Relevance
“…In small MAs, the majority (≈60%) of TRPV4 sparklet sites occurred at endothelial projections to SMCs or MEPs,5 where IK channels were also localized 1, 5. In small PAs, however, a small percentage of sparklet sites (25±3%; n=5 PAs) occurred at the MEPs.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…In small MAs, the majority (≈60%) of TRPV4 sparklet sites occurred at endothelial projections to SMCs or MEPs,5 where IK channels were also localized 1, 5. In small PAs, however, a small percentage of sparklet sites (25±3%; n=5 PAs) occurred at the MEPs.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies of endothelial Ca 2+ signals have demonstrated that localized Ca 2+ signals predominantly activate IK and SK channels to cause vasodilation in small systemic arteries including mesenteric, cremaster, and cerebral arteries 1, 2, 3, 4, 56. In small PAs, TRPV4 sparklets preferentially activated eNOS to cause vasodilation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations